2015
DOI: 10.1007/s10295-015-1670-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess for efficient production of recombinant Pichia anomala phytase and its applicability in dephytinizing chick feed and whole wheat flat Indian breads

Abstract: The phytase of the yeast Pichia anomala (PPHY) is a suitable biocatalyst as a food and feed additive because of its adequate thermostability, acid stability, protease insensitivity and broad substrate spectrum. The cell-bound nature and low phytase titres are the main bottlenecks for its utility in food and feed industries. In this investigation, we have overcome the problems by constitutive secretory expression of PPHY under glyceraldehyde phosphate dehydrogenase (GAP) promoter. A ~44-fold increase in rPPHY t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Very similar parameters were reported to produce L-asparaginase from another P. aeruginosa strain, where 1% (w/v) asparagine and glucose were reported for the maximum productivity after 48 hrs incubation at 35 °C (Amany et al 2021). Statistical optimization using PB and Response Surface Methodology (RSM) is always beneficial to understand the interaction among the physical and chemical parameters for enhancing the production of enzymes (Sharma and Satyanarayana 2011;Joshi and Satyanarayana 2015;Talluri et al 2019). Here, the results of this study observed maximum Lasparaginase production from 19.55±2.77 nM/min (4 th run) to 521.33±4.07 nM/min units (10 th run) during the PB analysis.…”
Section: Discussionmentioning
confidence: 69%
“…Very similar parameters were reported to produce L-asparaginase from another P. aeruginosa strain, where 1% (w/v) asparagine and glucose were reported for the maximum productivity after 48 hrs incubation at 35 °C (Amany et al 2021). Statistical optimization using PB and Response Surface Methodology (RSM) is always beneficial to understand the interaction among the physical and chemical parameters for enhancing the production of enzymes (Sharma and Satyanarayana 2011;Joshi and Satyanarayana 2015;Talluri et al 2019). Here, the results of this study observed maximum Lasparaginase production from 19.55±2.77 nM/min (4 th run) to 521.33±4.07 nM/min units (10 th run) during the PB analysis.…”
Section: Discussionmentioning
confidence: 69%